Experimental and numerical investigation on the dynamic response of a simplified open floating slender structure subjected to underwater explosion bubble. (1st January 2021) - Gan, N.; Liu, L.T.; Yao, X.L.; Wang, J.X.; Wu, W.B.
Abstract: A simplified open floating slender structure is used to investigate the dynamic behaviors of the warship in this paper. The deformation and damage mechanisms of the simplified open floating slender structure subjected to the underwater explosion are studied using the experiment and the Coupled Eulerian-Lagrangian (CEL) method. Firstly, a validation for the CEL method is carried out, where the numerical results agree well with the results in experiment. Subsequently, in order to analyze the deformation and damage characteristics of the simplified open floating slender structure subjected to the underwater explosion, a series of cases for different detonation distances and different charge weights are carried out. In the cases, the results indicate that the deformation and damage of the simplified open floating slender structure are mainly induced by the bubble, and the damage induced by the shock wave is not obvious. For small charge weight and large detonation distance, the whipping motion is the main deformation form of the simplified open floating slender structure. When the charge weight increases or the detonation distance decreases to a critical value, the simplified floating slender structure is damaged in a longitudinal bending mode with a plastic hinge generated in the middle region. Highlights: The deformation characteristics of a slender structure are investigated experimentally and numerically, and the results calculated by the CEL method agree well with the experimental results. The influences of the charge weight and the detonation distance on the dynamic response of the slender structure are investigated. The whipping motion and the longitudinal bending damage mode with a plastic hinge of the slender structure are analyzed. When close to the slender structure, the mushroom-like explosion bubble is split into two sub-bubbles by the annular sideway jets, and two jets toward opposite directions are generated.